Modification entropy of Kerr–Sen-like black hole in Lorentz-breaking bumblebee gravity - Tan, Xia; Wang, Cong; Yang, Shu-Zheng (Frontiers in Physics, 2024)
The Lorentz-breaking theory not only affects the space-time background, but also affects the dynamic behavior of bosons and fermions in curved space-time. Therefore, the Lorentz-breaking theory will affect the quantum tunneling rate, Hawking temperature, black hole entropy and other physical quantities of black holes. According to the modification of the space-time background and the modification of the particle dynamic equations, the quantum tunneling radiation of Kerr-Sen-like black hole in bumblebee gravitational theory and its related contents are deeply studied.The research methods and a series of new results obtained in this paper are discussed. This makes the research methods and conclusions in this paper are of more astrophysical significance and reference value.